Performance of medical schools in Mexico: Results from the Examen Nacional para Aspirantes a Residencias Médicas - Aldo Barajas-Ochoa; César Ramos-Remus; Stephanie Ramos-Gómez; Zalathiel Barajas-Ochoa; Jorge Manuel Sánchez-González; Mauricio Hernández-Ávila; José Ángel Córdova-Villalobos (Instituto Nacional de Salud Pública, 2019)
Objective. To assess the performance of medical schools (FEM) by analyzing the results of their applicants in the Examen Nacional para Aspirantes a Residencias Médicas (ENARM). Materials and methods. Five performance criteria, two official and three created on purpose, were calculated from the ENARM-2016 and -2017 official databases to assess FEM performance. Results. In 2016 and 2017, applicants registered from 112 and 115 FEM, respectively. Depending on the performance criteria, the FEM in the first place obtained 5 to 20 points more than the one placed second, and 23 to 98 points more than the FEM in the last place. Approximately 25% applicants were classified as "knowledge-deficient," and about 80% of these originated from less than one third of the FEM. Conclusion. The ENARM results provide information on the performance of the FEM. Approximately one of every four applicants obtained scores lower than the approval threshold of any specialty.